Synthesis of Alkyl Thiochromano[2,3-c]pyrrole-9-carboxylate Derivatives Utilizing Benzo[b]thiofuran-2,3-dione, Maleimides, and Alkyl Alcohol/Water Mixtures - Abadleh, Mohammed M.; Zahra, Jalal A.; Sabri, Salim S.; Abuzaid, Rania R.; Schollmeyer, Dieter; El-Abadelah, Mustafa M. (Synthesis, 2024)
A set of thiochromano[2,3-c]pyrrolidine-1,3-diones, incorporating α-hydroxy esters and their acids at the C-9 position, was prepared via direct interaction involving benzo[b]thiofuran-2,3-diones, maleimides, and alkyl alcohols in water at 90 °C. Structures of the new products were deduced from HRMS and NMR spectral data and confirmed by single-crystal X-ray crystallography. An insight into a proposed pathway involving a sequential Michael conjugate addition (initiated by the sulfur atom) and an aldol-type reaction is presented.
Keywords: benzo[b]thiofuran-2,3-dione; N-substituted maleimides; domino Michael–aldol reactions; thiochromano[2,3-c]pyrrolidines; ring expansion